Recasting Folk in the Himalayas : Indian Music, Media, and Social Mobility - Fiol, Stefan Patrick (University of Illinois Press, 2017)
"Colonialist, nationalist, and regionalist ideologies have profoundly influenced folk music and related musical practices among the Garhwali and Kumaoni of Uttarakhand. Stefan Fiol blends historical and ethnographic approaches to unlock these influences and explore a paradox: how the "folk" designation can alternately identify a universal stage of humanity, or denote alterity and subordination. Fiol explores the lives and work of Gahrwali artists who produce folk music. These musicians create art as both a discursive idea and a set of expressive practices across strikingly different historical and cultural settings. Juxtaposing performance contexts in Himalayan villages with Delhi recording studios, Fiol shows how the practices have emerged within and between sites of contrasting values and expectations. Throughout, he presents the varying perspectives and complex lives of the upper-caste, upper-class, male performers spearheading the processes of folklorization. But he also charts their resonance with, and collision against, the perspectives of the women and hereditary musicians most affected by the processes. Expertly observed, Recasting Folk in the Himalayas offers an engaging immersion in a little-studied musical milieu"--Back cover.
Keywords: Nepali people -- Music.; Nepali people -- Folklore.; Bhalara (Nepal) -- Social life and customs.; Népalais -- Musique.; Népalais -- Folklore.; HISTORY / Asia / India & South Asia.; SOCIAL SCIENCE / General; Manners and customs; Nepali people; Nepal -- Bhalara; Folklore; Music